1996
DOI: 10.1523/jneurosci.16-07-02157.1996
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between the C terminus of NMDA receptor subunits and multiple members of the PSD-95 family of membrane-associated guanylate kinases

Abstract: Selective concentration and anchoring of ionotropic receptors at the synapse is essential for neuronal signaling. Little is known about the molecules that mediate receptor clustering in the CNS. With use of the yeast two-hybrid system to screen a rat brain cDNA library and by in vitro binding assays, we have identified an interaction between NMDA receptor subunits 2A and 2B (NR2A and NR2B) and three distinct members of the PSD-95/SAP90 family of membrane-associated putative guanylate kinases. The interaction i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
562
1
3

Year Published

1998
1998
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 690 publications
(588 citation statements)
references
References 38 publications
22
562
1
3
Order By: Relevance
“…The PDZ domain is a module of about 90 amino acids designed to bind to other proteins (Sheng and Sala, 2001). One of the first PDZ proteins discovered, PSD-95, was shown to bind directly to the C-terminus of NR2 subunits in NMDA receptors and induced clustering of the receptors in cotransfected cells (Kornau et al, 1995;Niethammer et al, 1996). Whether PSD-95 is responsible for positioning native NMDA receptors at synapses in vivo is an open question, but it is clear that the protein can function as an organizing scaffold that tethers other components to the receptors (Tomita et al, 2001;Hung and Sheng, 2002).…”
Section: Localization Of Nicotinic Receptors On Neuronsmentioning
confidence: 99%
“…The PDZ domain is a module of about 90 amino acids designed to bind to other proteins (Sheng and Sala, 2001). One of the first PDZ proteins discovered, PSD-95, was shown to bind directly to the C-terminus of NR2 subunits in NMDA receptors and induced clustering of the receptors in cotransfected cells (Kornau et al, 1995;Niethammer et al, 1996). Whether PSD-95 is responsible for positioning native NMDA receptors at synapses in vivo is an open question, but it is clear that the protein can function as an organizing scaffold that tethers other components to the receptors (Tomita et al, 2001;Hung and Sheng, 2002).…”
Section: Localization Of Nicotinic Receptors On Neuronsmentioning
confidence: 99%
“…How might this subunit-specific trafficking be achieved? The anchoring protein, PSD-95, binds to the PDZ-binding domain that is common to all NR2 subunits (Niethammer et al, 1996;Sheng, 2001). One possible mechanism for trafficking the NR2A-and NR2B-containing NMDA receptors in opposite directions is that PSD-95 responds to NMDA receptor blockade with intramolecular structural changes, leading to an increased affinity of PSD-95 for the NR2A subunits and decreased affinity for the NR2B subunits.…”
Section: Nr2b and Nr2a Subunits Are Regulated Differentlymentioning
confidence: 99%
“…Among the NMDA receptor subunits, the NR1 is necessary for NMDA receptor function, but the NR2 subunits may be relatively more central in determining NMDA receptor localization (Mori et al, 1998;Steigerwald et al, 2000;Mohrmann et al, 2002) because their C-termini are longer and permit interaction with postsynaptic density (PSD) scaffolding proteins, such as PSD-95 (Niethammer et al, 1996;Bassand et al, 1999;Sheng and Pak, 2000). Among the NR2 subunits, the NR2A and NR2B subtypes are the most prevalent in the cerebral cortex (Watanabe et al, 1992), and of the two, the NR2B subunits are shown to be particularly influential in learning and memory (Tang et al, 1999;Tang and Schuman, 2002) as they prolong NMDA receptor currents, thus allowing greater Ca influx (Mori and Mishina, 1995;Dingledine et al, 1999).…”
mentioning
confidence: 99%
“…The ®rst two PDZ domains of PSD-95 have been shown to interact with the cytoplasmic tails of subunits of the NMDA glutamate receptor and of Shaker-type K + channels (Kim et al, 1995;Kornau et al, 1995;Niethammer et al, 1996). It has also been shown that the PDZ domains of FAP-1 mediate interaction with the C-terminus of Fas (Sato et al, 1995).…”
Section: Mapping Of the Domains Of Tax Mediating Interaction With Thementioning
confidence: 99%